School museums: an analysis of productions in postgraduate programs (Research, Society and Development, 2021)
The current work aimed to analyze the academic productions about school museums, in order to understand their role in Brazilian education and to draw an overview of the theme. School museums are spaces for the application of the intuitive teaching method, widespread in the first half of the 20th century. They are considered spaces for teaching, for application of new pedagogical methodologies, teacher training and school memory. They are divided into museums and offices of natural history, pedagogical museums, museums of school memory, including in their collection objects of memory and pedagogical resources. The period from the beginning of the twentieth century to the 1940s marks the most promising phase for this type of school institution. Its role in current education needs more foundation, especially in science teaching.